Editor's Choice – Follow-up of Patients After Revascularisation for Peripheral Arterial Diseases: A Consensus Document From the European Society of Cardiology Working Group on Aorta and Peripheral Vascular Diseases and the European Society for Vascular Surgery. (November 2019) - Venermo, Maarit; Sprynger, Muriel; Desormais, Ileana; Björck, Martin; Brodmann, Marianne; Cohnert, Tina; De Carlo, Marco; Espinola-Klein, Christine; Kownator, Serge; Mazzolai, Lucia; Naylor, Ross; Vlachopoulos, Charalambos; et al.
Abstract : Abstract: Peripheral arterial diseases comprise different clinical presentations, from cerebrovascular disease down to lower extremity artery disease, from subclinical to disabling symptoms and events. According to clinical presentation, the patient's general condition, anatomical location and extension of lesions, revascularisation may be needed in addition to best medical treatment. The 2017 European Society of Cardiology guidelines in collaboration with the European Society for Vascular Surgery have addressed the indications for revascularisation. While most cases are amenable to either endovascular or surgical revascularisation, maintaining long-term patency is often challenging. Early and late procedural complications, but also local and remote recurrences frequently lead to revascularisation failure. The rationale for surveillance is to propose the accurate implementation of preventive strategies to avoid other cardiovascular events and disease progression and avoid recurrence of symptoms and the need for redo revascularisation. Combined with vascular history and physical examination, duplex ultrasound scanning is the pivotal imaging technique for identifying revascularisation failures. Other non-invasive examinations (ankle and toe brachial index, computed tomography scan, magnetic resonance imaging) at regular intervals can optimise surveillance in specific settings. Currently, optimal revascularisation surveillance programmes are not well defined and systematic reviews addressing long-term results after revascularisation are lacking. We have systematically reviewed the literature addressing follow-up after revascularisation and we propose this consensus document as a complement to the recent guidelines for optimal surveillance of revascularised patients beyond the perioperative period.